A Behavioral and Electrophysiological Investigation of the Effect of Bilingualism on Lexical Ambiguity Resolution in Young Adults - Kousaie, Shanna; Laliberté, Christianne; López Zunini, Rocío; Taler, Vanessa (Frontiers in Human Neuroscience, 2015)
Previous research suggests that bilinguals demonstrate superior cognitive control processes than monolinguals. The goal of the current investigation was to examine whether this “bilingual advantage” is observed in a language processing task that requires inhibition, i.e., lexical ambiguity processing. Monolingual and bilingual participants read sentences that biased the reading of a terminal homonym toward the subordinate or dominant reading (e.g., The doctor asked her to step onto the scale.). A relatedness judgement was made on target words that were related to the contextually appropriate (e.g., balance) or inappropriate meaning (e.g., skin), or unrelated to either meaning (e.g., shoe) while electrophysiological recording took place. The results revealed subtle processing differences between monolinguals and bilinguals that were evident in electrophysiological measures, but not in behavioural measures. These findings suggest that monolinguals rely on context to access the contextually appropriate meaning of a homonym to a greater extent than bilinguals, while bilinguals demonstrate simultaneous activation of both meanings.